2022
DOI: 10.3390/ijms23137155
|View full text |Cite
|
Sign up to set email alerts
|

Early and Polyantigenic CD4 T Cell Responses Correlate with Mild Disease in Acute COVID-19 Donors

Abstract: We assessed SARS-CoV-2-specific CD4+ and CD8+ T cell responses in samples from 89 acute COVID-19 patients, utilizing blood samples collected during the first wave of COVID-19 in Italy. The goal of the study was to examine correlations between SARS-CoV-2-specific T cell responses in the early phase comparing mild, moderate, or severe COVID-19 disease outcomes. T cell responses to the spike (S) and non-S proteins were measured in a combined activation-induced marker (AIM) and intracellular cytokine staining (ICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Moreover, we have demonstrated that the specific cellular response against the domain 1 of spike (S1), measured at emergency room is a protective factor against severity (OR per 100 IFN-g sfu/10 6 PBMC increment: 0.47, 95%CI 0.20-0.87, p<0.05), independently of age and sex (61). These data suggest that for a total effective control of SARS-CoV-2 infection, an early induction of specific T cells within the first 7 days which peaks at 2 weeks PSO, followed by coordinated antibody production, is necessary (29,36,38,61,63). The disconnection between humoral and cellular immunity observed in severe patients (29,36,62) could be due to a delay in the innate immune response that may lead to a failure in T cell priming (19,20).…”
Section: Sars-cov-2-specific Cellular Response Protects Against Sever...mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, we have demonstrated that the specific cellular response against the domain 1 of spike (S1), measured at emergency room is a protective factor against severity (OR per 100 IFN-g sfu/10 6 PBMC increment: 0.47, 95%CI 0.20-0.87, p<0.05), independently of age and sex (61). These data suggest that for a total effective control of SARS-CoV-2 infection, an early induction of specific T cells within the first 7 days which peaks at 2 weeks PSO, followed by coordinated antibody production, is necessary (29,36,38,61,63). The disconnection between humoral and cellular immunity observed in severe patients (29,36,62) could be due to a delay in the innate immune response that may lead to a failure in T cell priming (19,20).…”
Section: Sars-cov-2-specific Cellular Response Protects Against Sever...mentioning
confidence: 98%
“…In addition to the long-term maintenance of specific T cell responses and their capacity to prevent severe disease (29,36,38,61,63), an increasing number of studies have demonstrated that infection-induced SARS-CoV-2-specific T cells largely tolerate the amino acid mutations of the different VoCs. The impact of the different mutations in the early VoCs (Alpha, Beta, Gamma, and Epsilon) is limited therefore the majority of CD4+ and CD8+ T cell responses are preserved (130-132).…”
Section: Duration Of T Cell Immunity and Its Potential Role In Protec...mentioning
confidence: 99%
“…The association between S-specific CD8 + T cell activation and viral kinetics is intriguing, suggesting that a greater magnitude of S-specific T cell recall may be associated with a more rapid clearance of virus in the URT. However, studies of monoclonal antibody administration indicate that antibody titres may also accelerate viral clearance (Weinreich et al, 2021). Therefore, we explored whether neutralising antibody levels (to the infecting or antigenically similar strain) was also associated with viral kinetics in this cohort.…”
Section: S-specific Cd8 + T Cell Activation Correlates With Viral Cle...mentioning
confidence: 99%
“…Infectivity of VIC01 stocks was determined by titration on Vero cells via cytopathic effect observation and calculated using the Reed-Muench method, as previously described (Juno et al, 2020). Infectivity of Omicron stocks was determined by titration on HAT-24 cells (a clone of transduced HEK293T cells stably expressing human ACE2 and TMPRSS2 (Tea et al, 2021)). In a 96-well flat bottom plate, virus stocks were serially diluted five-fold (1:5-1:78,125) in DMEM with 5% FCS, added with 30,000 freshly trypsinised HAT-24 cells per well and incubated at 37ºC.…”
Section: Sars-cov-2 Virus Propagation and Titrationmentioning
confidence: 99%
“…The role of cellular responses against SARS-CoV2 and other hCoVs is not fully understood [12], although emerging data suggest that robust T cell immunity correlates with rapid resolution of COVID-19 [13][14][15][16]. Competent adaptive cellular immunity alone may be sufficient for eradication of SARS-CoV2 and recovery from COVID-19 in subjects with profound acquired or inborn defects in B cell function [17].…”
Section: Introductionmentioning
confidence: 99%